The Wooded Lot : Homeowner and Builder Knowledge Perceptions in Selected Central Wisconsin Subdivisions - Vander Weit, William J. (University of Wisconsin-Stevens Point, College of Natural Resources, 1984)
Homeowners in 4 selected subdivisions in the village and township of Plover, Wisconsin, and builders around the area of Stevens Point, Wisconsin were surveyed. Each of the groups received separate questionnaires to explore attitudes involved in purchasing wooded lots, and to determine to what extent homeowners and builders understand the wooded ecosystem. Factors tied to the natural features of the lot had a greater role in influencing homebuyers than did other more functional factors such as accessibility. Homeowners valued trees primarily for their aesthetic qualities and contribution to property values. Trees on home lots were c9mmonly misidentified and the removal of small diameter tree and understory was common. Homeowners fared poorly on questions dealing with various aspects of the lot environment. Builders engaged in a variety of activities which posed potential problems for trees, and the overall knowledge of builders to safeguard trees and associated vegetation during development was low. Ordinances to protect woodlands and tree groupings during development were proposed, as were seminars for builders and homeowners which would address basic tree physiology and related aspects of the woodland environment.